Tracing the origin of Spanish common bean cultivars using biochemical and molecular markers - Ocampo Nahar, César H.; Martin, J,P,; Sánchez Yélamo, María Dolores; Ortíz, J.M.; Toro Chica, Orlando (Springer, 2005)
Fifty-four accessions of Phaseolus vulgaris cultivated in Spain and representing a broad variability for this country, were studied together with 30 samples of wild forms of American origin. Two reference cultivars (from the Andes and Mesoamerica) plus two outgroups (P. coccineus and Vigna unguiculata) were also included. RAPD analysis of DNA leaf extracts were carried out with four selected primers. We also studied morphological characters of the seeds and the phaseolin electrophoretic patterns. Multivariate analysis with the UPGMA method using RAPD data clustered the samples in four groups and, comparing with morphological data and phaseolin types, showed that the Spanish cultivars were mainly of Andean origin. Nevertheless, occurrence of introgression in Spain and the consideration of the country as a second center of variability for beans can also explain the obtained results.